Fishbowl Health Education Improved Mothers’ Knowledge of Recurrent Acute Respiratory Infection Prevention in Toddlers - Eka Diana Permatasari; Arif Rakhman; Rizky Rakhma Hidayah; Nurhakim Yudhi Wibowo (Poltekkes Kemenkes Surakarta, 2026)
ABSTRACT Background: Recurrent acute respiratory infections (ARI) remain a common health problem in early childhood and are closely associated with inadequate maternal knowledge of preventive practices. Fishbowl education is an interactive group learning method in which a small inner circle actively discusses a topic while the outer circle observes and provides feedback. This study aimed to examine the effect of fishbowl-based health education on mothers’ knowledge regarding the prevention of recurrent ARI among toddlers. Methods: A quasi-experimental study with a pretest-posttest control group design was conducted in Kertayasa Village, Central Java, Indonesia. Sixty mothers of toddlers with a history of recurrent ARI were assigned to an intervention group receiving fishbowl-based health education (n = 30) or a control group receiving lecture-based education (n = 30) through lottery allocation. Mothers’ knowledge was measured using a validated and reliable questionnaire. Data were analyzed using the Wilcoxon signed-rank test and the Mann-Whitney U test. Results: Knowledge increased significantly in the intervention group after fishbowl-based education (p < 0.001). Posttest scores in the intervention group were also significantly higher than those in the control group (p < 0.001), indicating that the fishbowl method was more effective than the lecture method. Conclusion: Fishbowl-based health education significantly improved mothers’ knowledge regarding recurrent ARI prevention among toddlers and may be a useful strategy for community health promotion.